Resistance to the Adoption of Advertising by Dermatologists and Plastic Surgeons - LaBarbera, Priscilla A. (Institutional Knowledge at Singapore Management University, 1987)
The article reports on a study to determine physician resistance to advertising by applying diffusion of innovation theory. Advertising was examined as an innovative service for physicians and was examined based on those factors which usually affect the adoption of an innovation. Results showed that while both dermatologists and plastic surgeons are concerned about the opportunity costs of not advertising, there are distinctions on how the two medical specialties view advertising. Dermatologists appear to be more patient and health oriented. Plastic surgeons seem be more concerned about economics and business. Thus, dermatologists are more likely to use advertising if there is a positive effect on the quality of health care, while plastic surgeons' likelihood of advertising is affected by their perceptions on the negative effects of abuse of advertising.